Comparison of propofol–hydromorphone and propofol–dexmedetomidine in patients with intubation after maxillofacial plastic surgery - Peng W; Zhang T; Wang Y (Dove Medical Press, 2016)
Wei Peng,1,2 Tiejun Zhang,2 Yanlin Wang1 1Department of Anesthesiology, Zhongnan Hospital, 2Department of Anesthesiology, School and Hospital of Stomatology, Wuhan University, Wuhan, Hubei, People’s Republic of China Objective: To compare the sedation and analgesic effects between propofol–hydromorphone and propofol–dexmedetomidine in patients with postoperative intubation after maxillofacial plastic surgery.Methods: Forty-two patients undertaking maxillofacial plastic surgery with intubation were randomly assigned into propofol plus hydromorphone (P–H) group or propofol plus dexmedetomidine (P–D) group, receiving intravenous infusion of P–H or P–D, respectively. Cerebral state index, Ramsay sedation score, arterial blood gas analysis, and physiology indices were recorded before admission (T0), 30 minutes (T1), 1 hour (T2), 2 hours (T3), 6 hours (T4), and 12 hours after admission (T5) to intensive care unit, and 10 minutes after extubation (T6). Blood interleukin-6 was measured with enzyme-linked immunosorbent assay.Results: There was no significant difference in arterial blood gas analysis, oxygen saturation, mean arterial pressure, and respiratory rate between two groups at all time-points (P>0.05). The changes of heart rate (at T4, T5, and T6), cerebral state index (T1, T2, T3, T4, and T5), and Ramsay score (at T3) in P–H group were significantly different from that in P–D group (P<0.05). The plasma interleukin-6 at T4 in P–H group was significantly lower than that in P–D group (P<0.05).Conclusion: The P–H approach takes advantages over P–D approach in relieving the pain and discomfort, reducing the overstimulation of sympathetic nerve and the stress level, and enhancing the tolerance of postoperative intubation after maxillofacial plastic surgery. Keywords: maxillofacial plastic surgery, intubation, hydromorphone, propofol, dexmedetomidine